"Breaking bad"? Gangs, masculinities, and murder in Trinidad. Issue 4 (8th August 2022) - Baird, Adam; Bishop, Matthew Louis; Kerrigan, Dylan
ABSTRACT: The murder rate in Port of Spain, Trinidad, rose dramatically around the turn of the millennium, driven overwhelmingly by young men in gangs in the city's poor neighborhoods. The literature frequently suggests a causal relationship between gang violence and rising transnational drug flows through Trinidad during this period. However, this is only part of a complex picture and misses the crucial mediating effect of evolving male identities in contexts of pronounced exclusion. Using original data, this article argues that historically marginalized "social terrains" are particularly vulnerable to violence epidemics when exposed to the influence of transnational drug and gun trafficking. When combined with easily available weapons, contextually constructed male hegemonic orders that resonate with the past act as catalysts for contemporary gang violence within those milieus. The study contributes a new empirical body of work on urban violence in Trinidad and the first masculinities-specific analysis of this phenomenon. We argue that contemporary gang culture is a historically rooted, contextually legitimated, male hegemonic street project in the urban margins of Port of Spain.